The Federalist papers : Alexander Hamilton, James Madison, John Jay - Hamilton, Alexander, 1757-1804; Madison, James, 1751-1836; Jay, John, 1745-1829; Shapiro, Ian; Horowitz, Donald L.; Hunt, Eileen M., 1971- (Rethinking the Western tradition., 2009)
"This authoritative edition of the complete texts of theFederalist Papers,the Articles of Confederation, the U.S. Constitution, and the Amendments to the U.S. Constitution features supporting essays in which leading scholars provide historical context and analysis. An introduction by Ian Shapiro offers an overview of the publication of the Federalist Papersand their importance. In three additional essays, John Dunn explores the composition of the Federalist Papers and the conflicting agendas of its authors; Eileen Hunt Botting explains how early advocates of women's rights, most prominently Mercy Otis Warren, Judith Sargent Murray, and Charles Brockden Brown, responded to the Federalist-Antifederalist debates; and Donald Horowitz discusses the Federalist Papers from the perspective of recent experiments with democracy and constitution-making around the world. These essays both illuminate the original texts and encourage active engagement with them." --